Red de cooperación técnica entre laboratorios de investigación y diagnóstico veterinario (FAO). - Arellano-Sota, Carlos (Avances en Ciencias Veterinarias, 1990)
In this technical note is presented the main characteristics and participants of technical cooperation network among veterinary research and diagnostic laboratories.